PENGARUH USIA HARAPAN HIDUP, HARAPAN LAMA SEKOLAH, DAN PENGELUARAN PERKAPITA TERHADAP INDEKS PEMBANGUNAN MANUSIA DI PROVINSI JAWA TENGAH - dzilkamil, khabibah; Adinugraha, Hendri (Universitas Halu Oleo, 2023)
This research aims to identify and test the influence of Life Expectancy, Expected Years of Schooling and Per Capita Income on the Human Development Index in Central Java Province. This research is expected to measure success in efforts to develop the quality of human life and determine the ranking or level of regional development in Central Java Province. The method used in this research is a quantitative approach. The independent variables in this research are Life Expectancy (X1), expected years of schooling (X2), and per capita income (X3). Meanwhile, the dependent variable in this research is the Human Development Index (Y). This research uses secondary data obtained from the Central Statistics Agency (BPS). Data processing techniques were carried out u…